PROBIOTIC SUPPLEMENTATION FOR THE RESTORATION OF INTESTINAL MICROBIOTA IN NEWBORNS BORN BY CESAREAN SECTION - Stepanović, Ivana; Radovanović, Jovana (HEALTH CARE, 2026)
The early establishment of intestinal microbiota in newborns is significantly disrupted in children born by cesarean section, characterized by the absence of beneficial anaerobic bacteria and an increased proportion of opportunistic microorganisms. This initial dysbiosis is associated with an increased risk of allergies, infections, and other immune imbalances. Probiotic supplementation represents a strategy to correct these disorders. The use of specific strains, particularly from the genera Lactobacillus and Bifidobacterium, can accelerate the colonization of the intestinal microbiota to resemble that of vaginally born children. These probiotics modulate the immune response, reducing the Th2 profile and promoting anti-inflammatory signals, while simultaneously strengthening the intestinal barrier and enhancing the production of short-chain fatty acids. Clinical data indicate positive effects, including a reduction in gastrointestinal complaints and the incidence of necrotizing enterocolitis in preterm infants, as well as improved immune markers. The mechanisms of action include competition for resources, production of bacteriocins, and interaction with immune cells. Although existing evidence supports the potential of probiotics in restoring the microbiota, variability in studies highlights the need for long-term monitoring and standardized protocols to fully assess health outcomes in this population.